Cellulose or chitin nanofibril-stabilized latex for medical adhesion via tailoring colloidal interactions. (15th February 2022) - Yang, Xianpeng; Yang, Shuang; Wang, Lei
Abstract: The objective of this research is to develop a functional medical adhesive from natural nanofibril-stabilized latex through an aqueous process. Surface charged cellulose or chitin nanofibrils are used to form Pickering emulsions of acrylic monomers, followed by in situ polymerization. Charged initiators are selected to tailor the interactions between them and nanofibrils, and it is found that the repulsive electrostatic interactions play a key role in stabilizing the heterogeneous system. As a result, poly(2-ethylhexyl acrylate- co -methyl methacrylate) latexes are successfully prepared for surfactant-free adhesives with a high shear strength of 72.0 ± 6.5 kPa. In addition, drug can be easily incorporated in the nanopaper substrate or adhesive layer to form a medical tape, exhibiting long-term drug release and antibacterial behaviors. We managed developing a facile method to integrate green synthesis, versatile functionalities and excellent adhesion into one adhesive, which remains a great challenge. Graphical abstract: Unlabelled Image